Providing appropriate health and social care for people with dementia or mild cognitive impairment in the criminal justice system of England and Wales: a thematic analysis of prisoner and staff interview data - Adam O’Neill; Leanne Heathcote; Laura Archer-Power; Stuart Ware; Jenny Shaw; Jane Senior; Katrina Forsyth (Health & Justice)
Abstract Background The number of older adults entering the criminal justice system is growing. Approximately 8% of older prisoners in England and Wales have suspected dementia or mild cognitive impairment (MCI) and experience difficulties in everyday functioning, and disruption to their daily life. At present, no specific dementia/MCI care pathway has been implemented that is applicable and appropriate for use across different prisons in England and Wales. The aim of this paper is to explore the experiences of older adults with dementia/MCI in prison, and a range of key stakeholders, around the day-to-day issues faced by people with dementia/MCI and prison, healthcare, and third sector staff regarding the delivery of support for individuals with dementia/MCI. Methods Thirty-two semi structured interviews were conducted with prison, local authority, and healthcare staff; peer supporters; third sector care providers; and individuals with dementia/MCI themselves, across five establishments, to provide multidimensional perspectives of dementia/MCI in criminal justice settings. The data obtained during interviews were thematically analysed. Results From the data, six key themes emerged: (I) ethical concerns around trial, sentencing and detainment for people with dementia/MCI; (II) An unforgiving prison system, providing physical and social environments incompatible with supporting individuals with dementia/MCI; (III) An unprepared workforce requiring training in dementia/MCI. (IV) A lack of collaboration leading to sub-optimum management of the support needs of people with dementia/MCI in prison; (V) Peer support ‘plugging the gap’; and (VI) staff ‘hands tied behind back’. Conclusions Results point towards a pressing need to develop more appropriate support systems for individuals with dementia/MCI throughout the criminal justice system. Ethical concerns around the judicial process for individuals with diminished cognitive capacity must be considered. Prison governors should examine ways to make the living environment more appropriate for these individuals, and a joined-up collaborative approach to health and social care should be adopted. Staff must be appropriately trained to support and identify individuals with dementia/MCI. Peer support schemes require formal evaluation, and training/oversight of these schemes should be comprehensive.